Menelusuri jejak ilmiah: Pemetaan bibliometrik dengan VOSviewer atas Corporate Tax Avoidance - rochmah, Ifa Datur (Maliki Interdisciplinary Journal, 2025)
This study aims to map the development of studies on corporate tax avoidance through a bibliometric approach using VOSviewer software. The research method used is quantitative between VOSviewer bibliometric analysis. Secondary data were obtained from 500 scientific articles published in the period 2019 to 2024, using the "Publish or Perish" application with the keyword "tax avoidance". The results of the VOSviewer visualization show that studies related to tax avoidance can be grouped into three main clusters that represent the focus and direction of the research. These findings provide an important contribution to understanding the literature map and identifying the direction of further research development.